Gradient chelation-free radical activation synergistic eucalyptus chemi-mechanical pulp wastewater composite coagulant and preparation method thereof
Through the composite coagulant preparation method of gradient chelation-free radical activation synergistically, the problem of unsatisfactory COD removal rate in the wastewater of eucalyptus chemical mechanical pulp is solved, and efficient and economical wastewater treatment effect is achieved.
Patent Information
- Application Number
- CN202510387890.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
In the prior art, when treating eucalyptus chemical mechanical pulp wastewater, the COD removal rate is not ideal, the cost is high, and the traditional water purification agent is large in doses and poor removal effect, making it difficult to meet the treatment needs.
A composite coagulant with a coordinated composite chelation-free radical activation was prepared by using ferrous sulfate heptahydrate, aluminum hydroxide and magnesium sulfate as raw materials. Through gradient chelation reaction, radical activation treatment, functional component composite reaction, pH and specific gravity regulation, and maturation treatment, a composite coagulant with a viscosity of 35~45 mPa·s was prepared.
The efficient treatment of eucalyptus slurry wastewater was achieved, with COD removal rate ≥83.5% and chromatic removal rate ≥88.7%, which significantly reduced the treatment cost and reduced the sludge volume.
Smart Images

Figure CN119898874A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of eucalyptus chemimechanical pulp wastewater treatment, and more specifically, relates to a gradient chelation-free radical activation synergistic eucalyptus chemimechanical pulp wastewater composite coagulant and a preparation method thereof. Background Art
[0002] Eucalyptus chemimechanical pulp is one of the main pulp types that pulp mills at home and abroad focus on developing. The production wastewater of this type of pulp is characterized by high chroma, high chemical oxygen demand (COD) and high water temperature. At present, the mainstream process flow of eucalyptus chemimechanical pulp wastewater treatment includes preliminary sedimentation, hydrolysis, anaerobic treatment, aerobic treatment, Fenton oxidation and final discharge. When treating eucalyptus chemimechanical pulp wastewater, COD becomes the main restrictive pollution indicator.
[0003] Taking the project of producing 200,000 tons of eucalyptus chemical mechanical pulp per year as an example, after aerobic treatment, the effluent COD concentration fluctuates between 1550mg / L and 1950mg / L, with an average of 1776mg / L and an average COD removal rate of 42.7%. In order to reduce the COD concentration from about 1776mg / L to below the discharge standard of 50mg / L, in actual operation, two-stage Fenton treatment is usually used. The first stage treatment reduces the COD to about 300mg / L, and the second stage treatment further reduces the COD to 40mg / L to 50mg / L. The cost of Fenton treatment is about 8 yuan / m 3 Up to 11 yuan / m 3 However, the Fenton reaction process has extremely strict requirements on reaction conditions and must be carried out under acidic pH conditions. After the reaction is completed, a large amount of alkaline substances must be added to adjust the pH to neutral. In addition, the use of ferrous sulfate leads to the generation of a large amount of chemical sludge during the treatment process, which not only makes the Fenton treatment process cumbersome and costly, but also may cause equipment corrosion and bring a large number of chemical sludge treatment problems.
[0004] Traditional water purifier products (such as polyaluminium chloride and polyferric sulfate) have shortcomings such as large dosage, unsatisfactory COD removal effect, and poor decolorization effect when treating eucalyptus chemical mechanical pulp wastewater, making it difficult to meet the treatment needs of chemical mechanical pulp wastewater. The Chinese invention patent with patent publication number CN109133303A discloses a COD removal rate of 65%~70%, but its chroma removal rate for eucalyptus chemical mechanical pulp wastewater is only 58%~62%, and the sludge moisture content is ≥85%. Although the Chinese invention patent with patent publication number CN112062257A increases the chroma removal rate to 75%, it needs to be used in conjunction with the Fenton process, resulting in a high cost (>8 yuan / m 3). The Chinese invention patent with patent publication number CN110563184A points out that PDMDAAC and formaldehyde resin are prone to phase separation due to the difference in charge density. Summary of the invention
[0005] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a preparation method of a composite coagulant for eucalyptus chemical mechanical pulp wastewater with gradient chelation-free radical activation synergy, and the preparation process is green and simple. Another technical problem to be solved by the present invention is to provide a composite coagulant prepared by the above preparation method, which performs well in treating eucalyptus chemical mechanical pulp wastewater. Another technical problem to be solved by the present invention is to provide the application of the above composite coagulant in the treatment of eucalyptus chemical mechanical pulp wastewater.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant, which uses ferrous sulfate heptahydrate, aluminum hydroxide and magnesium sulfate as raw materials, and obtains a water purifier with a viscosity of 35-45 mPa·s through gradient chelation reaction, free radical activation treatment, functional component composite reaction, pH and specific gravity regulation, and aging treatment; wherein the molar ratio of ferrous sulfate heptahydrate, aluminum hydroxide and magnesium sulfate is (8-10): (0.5-1.5): (0.5-1).
[0008] Preferably, the specific process of the gradient chelating reaction is: first add water, then add sulfuric acid into the reactor three times according to the gradient, dissolve ferrous sulfate heptahydrate, aluminum hydroxide and magnesium sulfate in sequence, control the reaction temperature to 50-60°C, and stir the reaction at a stirring speed of 700-900 rpm for 3 hours.
[0009] Preferably, the three additions of sulfuric acid are in a ratio of 6:3:1, with an interval of 10 to 15 minutes between each additions.
[0010] Preferably, the specific process of the free radical activation treatment is: after the gradient chelation reaction, an appropriate amount of sodium persulfate is added, and an oxidative polymerization activation reaction is carried out at a temperature of 60-70°C, and the dissolved oxygen concentration is controlled at 3-7 mg / L until Fe in the solution is 3+ :Fe 2+ The molar ratio is (9~19):1, stop adding sodium persulfate and end the reaction.
[0011] Preferably, the amount of sodium persulfate added is 0.8% to 2.5% of the total system mass.
[0012] Preferably, the specific process of the functional component composite reaction is: cooling the solution after free radical activation treatment by cooling and maintaining it at 40-50° C., adding polydimethyldiallylammonium chloride-formaldehyde dicyandiamide resin copolymer, stirring and mixing at a low speed to react, and obtaining a homogeneous composite solution.
[0013] The addition amount of the polydimethyldiallylammonium chloride-formaldehyde dicyandiamide resin copolymer is 1% to 3%.
[0014] Preferably, the preparation process of the polydimethyldiallyl ammonium chloride-formaldehyde dicyandiamide resin copolymer is as follows: polydimethyldiallyl ammonium chloride and formaldehyde dicyandiamide resin are mixed in a mass ratio of 5 to 20:1, reacted at 40 to 50°C for 2 to 4 hours, and stirred at a speed of 200 to 300 r / min. The polydimethyldiallyl ammonium chloride is a solution with an effective content of 40% and a molecular weight of 800,000 to 1.2 million Daltons.
[0015] Preferably, the specific process of regulating pH and specific gravity is: adjusting the pH of the system to 2-3 with concentrated sulfuric acid, and diluting the specific gravity to 1.3-1.4 with deionized water; the aging process is: subjecting the solution after regulating pH and specific gravity to gradient temperature controlled aging treatment, the first stage: cooling to 20°C at a rate of 1°C / min and maintaining for 3h; the second stage: heating to 38°C at a rate of 0.3°C / min and maintaining for 21h.
[0016] The composite coagulant is prepared by the method for preparing the composite coagulant for eucalyptus chemical-mechanical pulp wastewater with gradient chelation-free radical activation synergy.
[0017] Preferably, the composite coagulant comprises the following components in percentage by weight: (Fe 3+ / Fe 2+ ): 8%~10%, Al 3+ :0.5%~1.5%,Mg 2+ : 0.1%~0.5%, organic polymer: 1.5%~3.5%, the balance is water.
[0018] The composite coagulant is used in the treatment of eucalyptus chemical-mechanical pulping wastewater.
[0019] The application, according to the concentration of eucalyptus chemical mechanical pulp biochemical tail water, the dosage of the composite coagulant is controlled at 2-4 g / L, and the aeration operation is coordinated, and the aeration volume is 0.3-0.6 m 3 / h, aeration reaction 15~30min, to achieve effective treatment of eucalyptus chemical-mechanical pulping wastewater, sludge moisture content ≤80% after treatment, sludge volume reduction ≥30%
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1) The present invention adopts a gradient chelation-free radical activation composite process, realizes the molecular self-assembly of inorganic-organic components by controlling the reaction conditions in stages, and gradient chelation ensures the orderly complexation of metal ions to avoid competitive precipitation; creatively introduces sodium persulfate as a free radical initiator, cooperates with metal ions to construct a Fenton-like system, generates hydroxyl radicals (·OH), and cooperates with metal ions to degrade macromolecular organic matter; and then adopts a two-phase flocculant synergistic enhancement technology (PDMDAAC and formaldehyde dicyandiamide resin form a charge complementary structure) to prepare a liquid composite coagulant;
[0022] 2) The present invention utilizes the charge complementation mechanism of polydimethyldiallyl ammonium chloride (PDMDAAC) and formaldehyde dicyandiamide resin (PDMDAAC provides positive charge to neutralize the negative charge of the colloid, and formaldehyde dicyandiamide resin strengthens the adsorption bridging effect), and finds that PDMDAAC and formaldehyde resin can form a stable interpenetrating network structure within a specific mass ratio range (10-15:1), and maintain good stability in the system of the present invention, significantly enhancing the electrical neutralization ability of macromolecular colloid substances in wastewater, and effectively removing bio-refractory macromolecular substances in water;
[0023] 3) The composite coagulant of the present invention combines metal ions such as aluminum, iron, and magnesium with high molecular polymers to form a composite coagulant, which significantly improves the removal efficiency of organic pollutants and suspended solids, and performs well in treating eucalyptus chemical mechanical pulp wastewater; and under the same dosage conditions, its treatment effect significantly exceeds other similar products on the market, such as polyaluminum chloride (PAC) or polyferric sulfate (PFS);
[0024] 4) The product of the present invention works synergistically with the Fenton process, which can significantly enhance the efficiency of Fenton treatment and significantly reduce treatment costs; through the synergistic effects of gradient chelation, free radical activation and two-phase flocculation, a COD removal rate of ≥83.5% and a chromaticity removal rate of ≥88.7% are achieved in a single agent system;
[0025] 5) The present invention mainly utilizes industrial by-products as raw materials, has a simple production process, does not cause additional environmental pollution, and has good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of the composite coagulant prepared in Example 3. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following examples, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0028] The polydimethyldiallyl ammonium chloride used in the following examples is a solution with an effective content of 40% and a molecular weight of 800,000 to 1.2 million Daltons. The charge density ratio of polydimethyldiallyl ammonium chloride to formaldehyde dicyandiamide resin is (15 to 18) meq / g: (8 to 12) meq / g.
[0029] Example 1
[0030] A method for preparing a gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant comprises the following steps:
[0031] (1) Gradient chelation reaction: 400 mL of deionized water was added to the reactor, followed by 150 mL of 98% concentrated sulfuric acid added in three times (90 mL for the first time, 45 mL after an interval of 12 min, and 15 mL after an interval of 15 min). After each addition of acid, 200 g of ferrous sulfate heptahydrate, 80 g of aluminum hydroxide, and 15 g of magnesium sulfate were added in sequence. The temperature was controlled at 55 ± 1 °C by the jacket steam, the stirring speed was 800 ± 50 rpm, and the reaction was carried out for 3 h. The pH was monitored in real time and stabilized at 1.8-2.2 until a uniform solution was formed.
[0032] (2) Free radical activation treatment: 15 g of sodium persulfate was added to the homogeneous solution obtained in step (1), and the dissolved oxygen concentration was controlled at 5 mg / L by aeration. The temperature was raised to 70 °C for 1 h for oxidation activation reaction. The solution turned from light green to reddish brown until Fe 2+ / Fe 3+ The molar ratio reaches 1:19;
[0033] (3) 10 g of polydimethyldiallyl ammonium chloride and 0.5 g of formaldehyde dicyandiamide resin were mixed and reacted at 45 °C for 2 h with a stirring speed of 200-300 r / min to obtain polydimethyldiallyl ammonium chloride-formaldehyde dicyandiamide resin copolymer;
[0034] (4) Compounding of functional components: cooling the solution obtained in step (2) and maintaining the system temperature at 45° C., adding 1.0% (w / w) of the polydimethyldiallylammonium chloride-formaldehyde dicyandiamide resin copolymer obtained in step (3) to the solution, stirring and mixing at a low speed of 200-300 rpm for 1 h to obtain a homogeneous compound solution;
[0035] (5) pH and specific gravity control: The pH of the homogeneous composite solution obtained in step (4) was adjusted to 2.5 with concentrated sulfuric acid, and the specific gravity was diluted to 1.35 with deionized water. The solution after the pH and specific gravity were then aged. In the first stage, the temperature was lowered to 20°C at a rate of 1°C / min and maintained for 3 h. In the second stage, the temperature was raised to 38°C at a rate of 0.3°C / min and maintained for 21 h. A dark brown transparent liquid aluminum-iron-magnesium composite coagulant was obtained with a viscosity of 37.5 mPa·s.
[0036] Example 2
[0037] A method for preparing a gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant comprises the following steps:
[0038] (1) Add 400 mL of deionized water to the reactor, and then add 100 mL of 98% concentrated sulfuric acid to the reactor in three gradient additions (60 mL for the first time, 30 mL after an interval of 12 minutes, and 10 mL after an interval of 15 minutes). After each addition of acid, add 250 g of ferrous sulfate heptahydrate, 20 g of aluminum hydroxide, and 10 g of magnesium sulfate in sequence. Control the temperature at 60 °C and the stirring speed at 800 rpm. React for 3 hours and monitor the pH in real time to stabilize at 1.8-2.2 until a uniform solution is formed.
[0039] (2) Add 18 g of sodium persulfate to the homogeneous solution obtained in step (1), control the dissolved oxygen concentration at 5 mg / L by aeration, raise the temperature to 70°C for 1 hour for oxidation activation reaction, and the solution turns from light green to reddish brown until Fe 2+ / Fe 3+ The molar ratio is 1:10, and the reaction is terminated;
[0040] (3) 20 g of polydimethyldiallyl ammonium chloride and 2 g of formaldehyde dicyandiamide resin were mixed and reacted at 45 °C for 2 h with a stirring speed of 200-300 r / min to obtain polydimethyldiallyl ammonium chloride-formaldehyde dicyandiamide resin copolymer;
[0041] (4) cooling the solution obtained in step (2) and maintaining the system temperature at 40° C., adding 2.0% (w / w) of the polydimethyldiallylammonium chloride-formaldehyde dicyandiamide resin copolymer obtained in step (3) to the solution, stirring and mixing at a low speed of 200-300 rpm for 2 h to obtain a homogeneous composite solution;
[0042] (5) The pH of the homogeneous composite solution obtained in step (4) was adjusted to 2.1 with concentrated sulfuric acid, and the specific gravity was diluted to 1.38 with deionized water. The solution after adjusting the pH and specific gravity was then aged. In the first stage, the temperature was lowered to 20°C at a rate of 1°C / min and maintained for 3 hours. In the second stage, the temperature was raised to 38°C at a rate of 0.3°C / min and maintained for 21 hours to obtain a dark red-brown liquid high-iron composite coagulant with a viscosity of 41.9 mPa·s.
[0043] Example 3
[0044] A method for preparing a gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant comprises the following steps:
[0045] (1) Add 400 mL of deionized water to the reactor, and then add 130 mL of 98% concentrated sulfuric acid to the reactor in three gradient additions (78 mL for the first time, 39 mL after an interval of 12 minutes, and 13 mL after an interval of 15 minutes). After each addition of acid, add 160 g of ferrous sulfate heptahydrate, 10 g of aluminum hydroxide, and 20 g of magnesium sulfate in sequence. Control the temperature at 60 °C and the stirring speed at 800 rpm. React for 3 hours and monitor the pH in real time to stabilize at 1.8~2.2 until a uniform solution is formed.
[0046] (2) Add 12 g of sodium persulfate to the homogeneous solution obtained in step (1), control the dissolved oxygen concentration at 5 mg / L by aeration, raise the temperature to 70°C for 1 hour for oxidation activation reaction, and the solution turns from light green to reddish brown until Fe 2+ / Fe 3+ The ratio is 1:10, and the reaction is terminated;
[0047] (3) 20 g of polydimethyldiallyl ammonium chloride and 4 g of formaldehyde dicyandiamide resin were mixed and reacted at 40 °C for 3 h with a stirring speed of 200-300 r / min to obtain polydimethyldiallyl ammonium chloride-formaldehyde dicyandiamide resin copolymer;
[0048] (4) cooling the solution obtained in step (2) and maintaining the system temperature at 40 to 50° C., adding 2.0% (w / w) of the polydimethyldiallylammonium chloride-formaldehyde dicyandiamide resin copolymer obtained in step (3) to the solution, stirring and mixing at a low speed of 200 to 300 rpm for 1 to 2 hours to obtain a homogeneous composite solution;
[0049] (5) The pH of the homogeneous composite solution obtained in step (4) was adjusted to 2.5 with concentrated sulfuric acid, and the specific gravity was diluted to 1.3 with deionized water. The solution after adjusting the pH and specific gravity was then aged. In the first stage, the temperature was lowered to 20°C at a rate of 1°C / min and maintained for 3 hours. In the second stage, the temperature was raised to 38°C at a rate of 0.3°C / min and maintained for 21 hours to obtain a brown-red viscous liquid with a high decolorization function composite coagulant having a viscosity of 43.6 mPa·s.
[0050] Depend on Figure 1 It can be seen that the PDMDAAC-resin copolymer forms a three-dimensional network structure, which enhances the flocculation efficiency through adsorption bridging effect.
[0051] Example 4
[0052] The composite coagulant prepared in Examples 1-3 was compared with representative coagulants on the market, such as polyaluminium chloride (PAC), aluminium sulfate, polyferric sulfate, etc., using the effluent from the biochemical treatment of eucalyptus CTMP wastewater from a certain factory for coagulation comparison test. The dosage of the composite coagulant was 3000 mg / L, and the aeration operation was performed with an aeration volume of 0.3-0.6 m 3 / h, aeration time is 15~30min, the results are shown in Table 1.
[0053] Table 1 Coagulation effect of biochemical effluent from eucalyptus CTMP wastewater
[0054]
[0055] It can be seen from Table 1 that under the same dosage of the composite coagulant of the present invention, the COD and chroma removal rates of the three embodiments are significantly improved, and the sludge moisture content is significantly reduced, indicating that the composite coagulant prepared by the present invention can significantly improve the removal efficiency of COD and chroma of eucalyptus wastewater.
[0056] Comparative Example 1 (free radical activation treatment not used)
[0057] A method for preparing a composite coagulant for eucalyptus chemical-mechanical pulp wastewater comprises the following steps:
[0058] (1) Add 400 mL of deionized water to the reactor, and then add 100 mL of 98% concentrated sulfuric acid to the reactor in three gradient additions (60 mL for the first time, 30 mL after an interval of 12 minutes, and 10 mL after an interval of 15 minutes). After each addition of acid, add 250 g of ferrous sulfate, 20 g of aluminum hydroxide and 10 g of magnesium sulfate in sequence. Control the temperature at 60 °C and the stirring speed at 800 rpm. Stir the reaction for 3 hours. Real-time monitoring of pH is stable at 1.8~2.2 to form a uniform solution.
[0059] (2) Oxygen was introduced and the system was subjected to catalytic oxidation reaction at 90-100°C for 3 h. The solution turned from light green to reddish brown until Fe 2+ / Fe 3+ The molar ratio is 1:10, oxygen is stopped and the reaction is terminated;
[0060] (3) 20 g of polydimethyldiallyl ammonium chloride and 2 g of formaldehyde dicyandiamide resin were mixed and reacted at 45 °C for 2 h with a stirring speed of 200-300 r / min to obtain polydimethyldiallyl ammonium chloride-formaldehyde dicyandiamide resin copolymer;
[0061] (4) cooling the system and maintaining the system temperature at 40-50° C., adding 2.0% of the polydimethyldiallylammonium chloride-formaldehyde dicyandiamide resin copolymer obtained in step (3) to the solution, and stirring the mixture at a low speed of 200-300 rpm for 1-2 hours to achieve homogeneous compounding;
[0062] (5) The pH of the homogeneous composite solution obtained in step (4) was adjusted to 2.1 with concentrated sulfuric acid, and the specific gravity was diluted to 1.38 with deionized water. The solution after adjusting the pH and specific gravity was then subjected to aging treatment. The first stage was to cool the solution to 20°C at a rate of 1°C / min and maintain the solution for 3 hours. The second stage was to heat the solution to 38°C at a rate of 0.3°C / min and maintain the solution for 21 hours. A dark brown liquid water purifier was obtained with a viscosity of 41.1 mPa·s.
[0063] Example 5
[0064] The composite coagulant prepared in comparative example 1 and the composite coagulant obtained in example 2 were used to treat the effluent of the eucalyptus CTMP wastewater (reddish brown in appearance, pH 8.31, COD Cr 1586mg / L, chromaticity 1250 times) was used for coagulation comparison test, and the results are shown in Table 2.
[0065] Table 2 Comparative data of treatment effects of comparative example 1 and embodiment 2
[0066]
[0067] As shown in Table 2, the composite coagulant prepared in Example 2 of the present invention has better removal effects on COD and chromaticity when the composite coagulant is added in the same dosage as the composite coagulant prepared in Comparative Example 1, and the effluent COD and chromaticity are lower, indicating that the absence of hydroxyl radicals leads to a significant decrease in the removal of macromolecular organic matter to varying degrees. The free radical activation process contributes to a COD removal rate of 12.1% and a chromaticity removal rate of 32.5%, which is the core of treating refractory substances. In-situ infrared spectroscopy tracking shows that in Example 2, COC bonds (1260cm -1) intensity decreased by 78%, while that of comparative example 1 only decreased by 23% during the same period of time, indicating that the absence of free radicals significantly delayed the decomposition process of macromolecules.
[0068] Example 6
[0069] The process of the free radical concentration-treatment effect correlation experiment is as follows: 400 mL of deionized water was added to the reactor, and then 100 mL of 98% concentrated sulfuric acid was added to the reactor in three gradients (60 mL for the first time, 30 mL after an interval of 12 minutes, and 10 mL after an interval of 15 minutes). After each addition of acid, 250 g of ferrous sulfate, 20 g of aluminum hydroxide and 10 g of magnesium sulfate were added in sequence. The temperature was controlled at 60 ° C, the stirring speed was 800 rpm, and the reaction was stirred for 3 hours. The pH was monitored in real time and stabilized at 1.8~2.2 to form a uniform solution; sodium persulfate accounting for 0~2% of the total mass of the system was added to the obtained uniform solution, and the dissolved oxygen concentration was controlled to 5 mg / L by air. The reaction was carried out at 70 ° C for 1 hour, and Fe 2+ / Fe 3+ The molar ratio (o-phenanthroline spectrophotometry) was used to detect the hydroxyl radical concentration using a fluorescent probe method. The results are shown in Table 3, where the amount of sodium persulfate added was 0 for comparative example 1 (control group), and the amount of sodium persulfate added was 1.5% for example 2.
[0070] Table 3 Treatment effects of different free radical concentrations
[0071]
[0072] As shown in Table 3, when the addition amount of sodium persulfate is ≥1.5%, the ·OH concentration exceeds 0.28 μmol / L, and the COD removal rate rises sharply (from 79.6% to 86.9%), proving that 1.2%~1.8% is the technical critical range. It is proved that the free radical activation process can effectively break through the limitation of traditional flocculants that only rely on electrical neutralization / adsorption, realize the oxidation-flocculation synergistic treatment mechanism, and solve the technical bottleneck of low removal rate of colored refractory substances in existing traditional production technology.
[0073] Comparative Example 2 (High Molecular Copolymer Not Used)
[0074] A method for preparing a composite coagulant for eucalyptus chemical-mechanical pulp wastewater comprises the following steps:
[0075] (1) Add 400 mL of deionized water to the reactor, and then add 130 mL of 98% concentrated sulfuric acid to the reactor in three gradient additions (78 mL for the first time, 39 mL after an interval of 12 minutes, and 13 mL after an interval of 15 minutes). After each addition of acid, add 160 g of ferrous sulfate heptahydrate, 10 g of aluminum hydroxide and 20 g of magnesium sulfate in sequence. Control the temperature at 60 °C and the stirring speed at 800 rpm. Stir the reaction for 3 hours. Real-time monitoring of pH is stable at 1.8~2.2 to form a uniform solution.
[0076] (2) Add 12 g of sodium persulfate to the homogeneous solution obtained in step (1), control the dissolved oxygen concentration at 5 mg / L by aeration, raise the temperature to 70°C for 1 hour for oxidation activation reaction, and the solution turns from light green to reddish brown until Fe 2+ / Fe 3+ The molar ratio is 1:10, and the reaction is terminated;
[0077] (3) Add 24 g of deionized water to the solution obtained in step (2), adjust the pH of the solution to 2.5 with concentrated sulfuric acid, dilute the specific gravity to 1.3 with deionized water, and then perform a aging treatment on the solution after adjusting the pH and specific gravity. In the first stage, cool the temperature to 20°C at a rate of 1°C / min and maintain for 3 hours; in the second stage, heat the temperature to 38°C at a rate of 0.3°C / min and maintain for 21 hours to obtain a composite coagulant with a viscosity of 30.4 mPa·s.
[0078] Example 7
[0079] The composite coagulant prepared in Comparative Example 2 and the composite coagulant obtained in Example 3 were used to treat the effluent of the eucalyptus CTMP wastewater (reddish brown in appearance, pH 8.31, COD Cr 1586mg / L, chromaticity 1250 times) was used for coagulation comparison test, and the results are shown in Table 4.
[0080] Table 4 Comparative data of treatment effects of comparative example 2 and embodiment 3
[0081]
[0082] As shown in Table 4, the COD removal rate decreased by 10.2%, the chromaticity removal rate decreased by 24.9%, and the charge neutralization capacity decreased by 49.7%. The reduction in the removal rate of chromatic macromolecular substances verifies the specific capture of lignin and other substances containing chromophores by the adsorption and bridging effect of the polymer copolymer.
[0083] Comparative Example 3 (without gradient chelation)
[0084] A method for preparing a composite coagulant for eucalyptus chemical-mechanical pulp wastewater comprises the following steps:
[0085] (1) Add 400 mL of deionized water to the reactor, add 150 mL of 98% concentrated sulfuric acid to the reactor all at once, add 200 g of ferrous sulfate heptahydrate, 80 g of aluminum hydroxide and 15 g of magnesium sulfate, control the temperature to 55 °C, stir at 800 rpm, stir and react for 3 h to form a uniform solution;
[0086] (2) Add 15 g of sodium persulfate to the homogeneous solution obtained in step (1), control the dissolved oxygen concentration at 5 mg / L by aeration, raise the temperature to 70°C for 1 h, and perform oxidation activation reaction until the solution changes from light green to reddish brown. 2+ / Fe 3+ The molar ratio reaches 1:19;
[0087] (3) 10 g of polydimethyldiallyl ammonium chloride and 0.5 g of formaldehyde dicyandiamide resin were mixed and reacted at 45 °C for 2 h with a stirring speed of 200-300 r / min to obtain polydimethyldiallyl ammonium chloride-formaldehyde dicyandiamide resin copolymer;
[0088] (4) cooling the solution obtained in step (2) and maintaining the system temperature at 45° C., adding 1.0% of the polydimethyldiallylammonium chloride-formaldehyde dicyandiamide resin copolymer obtained in step (3) to the solution, stirring and mixing at a low speed of 200-300 rpm for 1 h to obtain a homogeneous composite solution;
[0089] (5) The homogeneous composite solution obtained in step (4) was additionally adjusted to pH 2.5 with concentrated sulfuric acid, and the specific gravity was diluted to 1.35 with deionized water. The solution after adjusting the pH and specific gravity was then subjected to an aging treatment. In the first stage, the temperature was lowered to 20°C at a rate of 1°C / min and maintained for 3 hours. In the second stage, the temperature was raised to 38°C at a rate of 0.3°C / min and maintained for 21 hours. A dark brown liquid aluminum-iron-magnesium composite water purifier was obtained with a viscosity of 37.3 mPa·s.
[0090] Example 8
[0091] The composite coagulant prepared in comparative example 3 and the composite coagulant obtained in example 1 were used to treat the effluent of the eucalyptus CTMP wastewater (reddish brown in appearance, pH 8.31, COD Cr 1586mg / L, chromaticity 1250 times) was used for coagulation comparison test, and the results are shown in Table 5.
[0092] Table 5 Comparative data of treatment effects of Comparative Example 3 and Example 1
[0093]
[0094] As shown in Table 5, the gradient chelation process increased the COD removal rate by 6.2% in absolute value and 7.9% in relative value. The non-gradient process caused the metal ion dissolution to exceed about 2 times, which posed a risk of secondary pollution. The staged acid addition control extended the effective period of the agent from 6 months to 12 months, and the stability was increased by 1 times. Gradient ion chelation can avoid metal ion competition precipitation as much as possible; it can achieve pH buffer control and maintain the best reaction environment; it can achieve orderly assembly and build a stable composite structure.
[0095] Comparing Example 1 with Comparative Example 3, it was found through online pH monitoring that the pH of the system was stable at 1.8-2.2 during gradient chelation, while the pH dropped sharply (<1.5) during non-gradient chelation, resulting in premature dissolution of aluminum hydroxide to form Al 3+ Instead of Al(OH)3 colloid. Chelation degree analysis by EDTA titration method: metal chelation degree of Example 1: 98.2%, metal chelation degree of Comparative Example 3: 72.5%, gradient chelation improves metal ion complexation efficiency by 35.5%. The particle size distribution results detected by laser particle size analyzer are shown in Table 6.
[0096] Table 6 Particle size distribution results of Comparative Example 3 and Example 1
[0097]
[0098] As shown in Table 6, the non-gradient process easily leads to incomplete dissolution reaction of the raw materials, and the effective flocculation particles (1-100 μm) are reduced by 25.4%.
[0099] Example 9 (Comparative experiment of different sulfuric acid ratios in gradient chelation)
[0100] The preparation steps of Example 1 were adopted, the total amount of sulfuric acid was fixed at 150 mL, and the effects of different sulfuric acid distribution ratios (6:3:1, 4:4:2, 7:2:1) on the chelation degree, COD removal rate and metal dissolution were compared. The results are shown in Table 7.
[0101] Table 7 Effect of different sulfuric acid distribution ratios on performance
[0102]
[0103] As shown in Table 7, the ratio of 6:3:1 can significantly improve the metal chelation degree (21.9% compared with the ratio of 4:4:2) and perform better in terms of chemical oxygen demand (COD) removal rate. In addition, this ratio can effectively reduce the risk of secondary pollution, specifically, the amount of Fe³+ dissolved is reduced by 65.7%.
[0104] In summary, the results of Examples 1-3 and Comparative Examples 1-3 show that: 1) Necessity of gradient chelation: The metal chelation degree of Comparative Example 3 (non-gradient acid addition) is only 72.5%, resulting in Fe 3+ The dissolution amount is 2.1 times higher than that of the present invention (2.5 mg / L vs 1.2 mg / L); 2) Radical activation critical value: when the addition amount of sodium persulfate is less than 1.2% (Comparative Example 1), hydroxyl radicals are not detected and the COD removal rate decreases by 9.4%; 3) Copolymer synergistic effect: The chromaticity removal rate of Comparative Example 2 (without copolymer) decreases by 23.3%, proving that PDMDAAC-resin charge complementation is the core mechanism of decolorization.
[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a composite coagulant for eucalyptus chemical-mechanical pulping wastewater with gradient chelation-free radical activation synergy, characterized in that: Ferrous sulfate heptahydrate, aluminum hydroxide and magnesium sulfate are used as raw materials, and a water purifier with a viscosity of 35-45 mPa·s is prepared through gradient chelation reaction, free radical activation treatment, functional component complex reaction, pH and specific gravity adjustment, and aging treatment; wherein the molar ratio of ferrous sulfate heptahydrate, aluminum hydroxide and magnesium sulfate is (8-10): (0.5-1.5): (0.5-1).
2. The method for preparing the gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant according to claim 1, characterized in that: The specific process of the gradient chelation reaction is: first add water, then add sulfuric acid into the reactor three times according to the gradient, dissolve ferrous sulfate heptahydrate, aluminum hydroxide and magnesium sulfate in sequence, control the reaction temperature to 50-60°C, and stir the reaction at a stirring speed of 700-900 rpm for 3 hours.
3. The method for preparing the gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant according to claim 2, characterized in that: The three additions of sulfuric acid are in a ratio of 6:3:1, with an interval of 10 to 15 minutes between each addition.
4. The method for preparing the gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant according to claim 1, characterized in that: The specific process of the free radical activation treatment is: after the gradient chelation reaction, an appropriate amount of sodium persulfate is added, and an oxidative polymerization activation reaction is carried out at a temperature of 60-70°C, and the dissolved oxygen concentration is controlled at 3-7 mg / L until Fe 3+ :Fe 2+ The molar ratio is (9~19):1, stop adding sodium persulfate and end the reaction.
5. The method for preparing the gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant according to claim 1, characterized in that: The specific process of the functional component composite reaction is: cooling the solution after free radical activation treatment and maintaining it at 40-50° C., adding polydimethyldiallylammonium chloride-formaldehyde dicyandiamide resin copolymer, stirring and reacting at a low speed to obtain a homogeneous composite solution.
6. The method for preparing the gradient chelation-free radical activation synergistic eucalyptus chemical-mechanical pulp wastewater composite coagulant according to claim 1, characterized in that: The specific process of regulating pH and specific gravity is: adjusting the pH of the system to 2-3 with concentrated sulfuric acid, and diluting the specific gravity to 1.3-1.4 with deionized water; the aging process is: subjecting the solution after regulating pH and specific gravity to gradient temperature control aging treatment, the first stage: cooling to 20°C at a rate of 1°C / min and maintaining for 3h; the second stage: heating to 38°C at a rate of 0.3°C / min and maintaining for 21h.
7. The composite coagulant prepared by the method for preparing the composite coagulant for eucalyptus chemical-mechanical pulping wastewater by gradient chelation-free radical activation synergy according to any one of claims 1 to 6.
8. The composite coagulant according to claim 7, characterized in that The composite coagulant comprises the following components in percentage by weight: (Fe 3+ / Fe 2+ ): 8%~10%, Al 3+ :0.5%~1.5%,Mg 2+ : 0.1%~0.5%, organic polymer: 1.5%~3.5%, the balance is water.
9. Use of the composite coagulant according to claim 7 or 8 in the treatment of eucalyptus chemical-mechanical pulping wastewater.
10. The use according to claim 9, characterized in that: According to the concentration of eucalyptus chemical mechanical pulp biochemical tail water, the dosage of composite coagulant is controlled at 2~4g / L, and aeration operation is carried out with an aeration volume of 0.3~0.6m 3 / h, aeration reaction 15 ~ 30min, to achieve effective treatment of eucalyptus chemical-mechanical pulping wastewater, the sludge moisture content after treatment ≤ 80%, sludge volume reduction ≥ 30%.
Citation Information
Patent Citations
Heavy metal sewage precipitant
CN109133303A
Intelligent water purifier with alarm function
CN110563184A
Method for treating antibiotic wastewater by utilizing iron ion doped metal organic framework material
CN112062257A
Coagulant special for steelworks or power plant coking wastewater
CN101209872A
Coagulation decolourant for printing and dyeing waste water
CN101215029A
Cited By
Efficient liquid fluorine removal agent based on terpolymer
CN121085393A
A highly efficient liquid fluorine removal agent based on a terpolymer
CN121085393B